Characterization Of Raw Material (Glycerol Residue) And Escherichia Coli In Immobilized Cell For Succinic Acid Production - Nik Nor Aziati, Abdul Aziz; Mimi Sakinah, A. M. (Universiti Malaysia Pahang, 2016)
The use of glycerol residue, a palm oil waste from Oleochemical industries as a raw material for the production of succinic acid with immobilized cell fermentation process was investigated. In this work, the raw material, immobilized cells to produced succinic acid were characterized by Fourier Transform Infrared Spectrometry (FTIR) and Scanning Electron Microscope instruments. Based on the results, the functional group appearing for treated and commercial glycerol is the hydroxyl, aromatic methoxyl, alkenes, soap, carbonyl and alcohol group. The hydroxyl group which is O-H appeared at a spectra value of 3394.27 cm-1for the treated glycerol and 3299.96 cm-1 for the commercial group. Respectively. From the analysis of SEM for bead, it was found that majority of pores fall within range and the shapes was ellipsoid and a thick skin around strains was detectable, therefore indicating that immobilized cell prepared for fermnatation process is an attractive source for succinic acid applications